Composition dependent order-disorder transition in NdxZr1−xO2−0.5x pyrochlores: A combined structural, calorimetric and ab initio modeling study. (15th February 2017) - Finkeldei, S.; Kegler, Ph.; Kowalski, P.M.; Schreinemachers, C.; Brandt, F.; Bukaemskiy, A.A.; Vinograd, V.L.; Beridze, G.; Shelyug, A.; Navrotsky, A.; Bosbach, D.
Abstract: The order-disorder phase transition in the Ndx Zr1−x O2−0.5x system is studied by complementary techniques which include wet chemical synthesis of a series of compositions with various Nd/Zr ratios with the final annealing at 1873 K, X-ray diffraction, oxide melt solution calorimetry and ab initio thermodynamic modeling. Our structural data indicate the transition from ordered to disordered pyrochlore at x ∼0.31 at a temperature of 1873 K. Our calorimetric data show a transition enthalpy of ∼30 kJ/mol, which corresponds to an entropy of disordering of ∼16 J/K/mol. The latter value is significantly smaller than the configurational entropy of transition computed under the assumption of complete disorder in a fluorite phase, indicating a substantial degree of order remaining in the fluorite phase at the temperature of synthesis. The considered phases are computed ab initio using a series of special quasi-random structures that emulate the complete or partial disorder. The results of our calculations and thermodynamic modeling are in good agreement with the measured lattice parameters, the Nd content at the order-disorder transition, and the measured formation and transformation enthalpies. Thus our combined experimental and modeling results provide valuable insight into the disordering of this pyrochlore phase and of other pyrochlore materials. Graphical abstract: Image 1